Commentary on the decision of the Supreme Court, file No. I CSK 138/08 - Lisowska, Anna (Acta Universitatis Lodziensis. Folia Iuridica, 2018)
<span style="line-height: 115%; font-family: 'Calibri','sans-serif'; font-size: 11pt; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: 'Times New Roman'; mso-bidi-theme-font: minor-bidi; mso-fareast-language: EN-US; mso-bidi-font-style: italic; mso-ansi-language: PL; mso-bidi-language: AR-SA;">This article is a commentary on the court decisions made in connection with the factual situation regarding the admission of a patient to a psychiatric hospital without their consent. In relation to the circumstances found in the case, conditions determining the acceptability of admission to a psychiatric hospital with no consent were discussed under legal regulations contained in art. 23 and 24 of the mental health act. The publication presented arguments for the rightness of providing people with healthcare services, in some circumstances without their consent.